In vitro characterization and delivery of chitosan-DNA microparticles into mammalian cells. - (:unkn) unknown (CANADIAN SOC PHARMACEUTICAL SCIENCES, 2004)
Purpose: Chitosan has a high potential for transferring DNA molecules into mammalian cells because of its cationic properties. In the present study, we have investigated DNA encapsulation efficiency and loading capacity of chitosan microparticles prepared in different conditions, as well as in vitro DNA release from microparticles, and transfection of different cell lines with chitosan-DNA microparticles, which may be employed in future in vivo studies. Methods: Plasmid DNAs were amplified in Escherichia coli DH5alpha and isolated by the alkali SDS-lysis method. Chitosan-DNA microparticles were prepared by the coacervation method by using different concentrations of chitosan and plasmid DNAs. In vitro release experiments were performed in PBS at 37degreesC and DNA release was monitored spectrophotometrically. Transfection efficiency of chitosan-DNA microparticles into mammalian cells was determined by measuring the beta-galactosidase activity in cell lysates. Results: DNA encapsulation efficiency and loading capacity of microparticles was altered depending on the chitosan and DNA concentrations. Approximately 75-85% of DNA was encapsulated into the chitosan-DNA microparticles. The average size of microparticles was found to be similar to 2 mum. In vitro studies revealed that the release of DNA from chitosan microparticles could be controlled by changing the formulation conditions. Although the transfection efficiency of chitosan-DNA microparticles was typically lower than that of DNA complexed with lipid-based reagents, in vitro transfection results indicated that HEK293 cells take up chitosan-DNA microparticles more efficiently compared to HeLa and mouse fibroblastic 3T3 cell lines. Conclusion: Chitosan microparticles provide a sustained release of plasmid DNA for a long period and they have a potential for DNA transfer into the mammalian cells. However, transfection efficiency of chitosan-DNA microparticles is low and dependent on the cell type.
Keywords: GENE DELIVERY; TRANSFECTION EFFICIENCY; MOLECULAR-MASS; VIRAL VECTORS; NANOPARTICLES; THERAPY; MICROSPHERES; NANOSPHERES; EXPRESSION; COMPLEXES